2005
DOI: 10.1007/s00701-005-0590-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal degeneration and iNOS expression in experimental brain contusion following treatment with colchicine, dexamethasone, tirilazad mesylate and nimodipine

Abstract: The findings underscored that an early neuroprotective effect does not necessarily lead to increased long-term neuronal survival. The absence of a significant long-term effect with nimodipine and dexamethasone agrees with clinical studies. Colchicine with an anti-macrophage/anti-inflammatory activity and the free radical scavenger tirilazad mesylate were effective for amelioration of experimental contusion with moderate energy transfer. Early neuroprotection may to some extent target iNOS via different pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 165 publications
(241 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, omega-3 polyunsaturated fatty acids were shown to provide neuroprotection after stroke [32]. Gahm et al showed a significant decrease of degenerated neurons early after trauma linked to nimodipine, but also to colchicine, dexamethasone and tirilazad mesylate [33]. In the same study, the expression of iNOS (inducible nitric oxide synthase) was reduced by nimodipine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, omega-3 polyunsaturated fatty acids were shown to provide neuroprotection after stroke [32]. Gahm et al showed a significant decrease of degenerated neurons early after trauma linked to nimodipine, but also to colchicine, dexamethasone and tirilazad mesylate [33]. In the same study, the expression of iNOS (inducible nitric oxide synthase) was reduced by nimodipine.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological identification and quantification of iNOS in DAB staining and immunofluorescence was performed according to our earlier studies [14,15,16,17]. The amount of positive cells was determined manually in the ROI by the same assessor in 400× magnification using a Leica DMRB and a DM400B microscope equipped with a DFC320 camera.…”
Section: Quantificationmentioning
confidence: 99%
“…65 The acute and long-lasting excessive quantities of NO release post-TBI are generated from iNOS and far outweigh the increases in eNOS and nNOS. [66][67][68] In vivo and in culture, iNOS was shown to augment the release of CGRP from trigeminal afferents. 69,70 However, considering the evidence for nNOS in migraine, as well as inflammatory pain studies, 26,71 it is reasonable to expect nNOS involvement in the pain pathway post-TBI.…”
Section: Trauma-induced Pain Signaling Molecules and Their Modulationmentioning
confidence: 99%